2009
DOI: 10.1111/j.1752-8062.2009.00074.x
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in Hematopoietic Microenvironment in Patients with Aplastic Anemia

Abstract: Mechanisms of hematopoietic failure in patients with aplastic anemia (AA) are obscure. We investigate alterations in the hematopoietic microenvironment in AA patients. We present the results of studying mesenchymal stromal cells (MSC), fibroblastic colony-forming units (CFU-F), and adherent cell layers (ACL) of long-term bone marrow cultures (LTBMC) from bone marrow (BM) samples of AA patients. MSC of AA patients proliferated longer than those of donors. In half of the patients' MSC cultures, adipogenesis was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…BM‐MSC are an essential component of the BM microenvironment and are pivotal for the balanced regulation of HSPC functions (Jing et al, 2010; Méndez‐Ferrer et al, 2010; Saleh et al, 2015; Walenda et al, 2010). We and a few other studies have reported morphologic, genetic and functional impairment of BM‐MSC in acquired AA (Chaturvedi et al, 2018; Hamzic et al, 2015; Huo et al, 2020; Li et al, 2012; Shipounova et al, 2009; Tripathy et al, 2014). Another report shows that BM‐MSC of AA patients when cocultured with CD34 + cells, reduced the proliferative and clonogenic potential of CD34 + cells (Hamzic et al, 2015).…”
Section: Discussionmentioning
confidence: 60%
“…BM‐MSC are an essential component of the BM microenvironment and are pivotal for the balanced regulation of HSPC functions (Jing et al, 2010; Méndez‐Ferrer et al, 2010; Saleh et al, 2015; Walenda et al, 2010). We and a few other studies have reported morphologic, genetic and functional impairment of BM‐MSC in acquired AA (Chaturvedi et al, 2018; Hamzic et al, 2015; Huo et al, 2020; Li et al, 2012; Shipounova et al, 2009; Tripathy et al, 2014). Another report shows that BM‐MSC of AA patients when cocultured with CD34 + cells, reduced the proliferative and clonogenic potential of CD34 + cells (Hamzic et al, 2015).…”
Section: Discussionmentioning
confidence: 60%
“…46 Our data are in partial disagreement with those of other studies suggesting that AA BM-MSC are aberrant. 8,41,42,44,46,48 From a methodological point of view, we assessed the features of AA BM-MSC beyond morphology, gene expression, differentiation potential and proliferation by analyzing the cells' ability to support hematopoiesis in vitro and in vivo and their immune properties. Biologically, all our patients, but one, were elderly patients while other studies focused on chil-BM-MSC in aplastic anemia haematologica | 2014; 99(7) dren/young adults with AA.…”
Section: Discussionmentioning
confidence: 99%
“…8,[41][42][43][44][45][46][47][48] These studies mainly claim that AA BM-MSC have aberrant morphology, impaired adipogenic and osteogenic potential, changes in gene expression, and a reduced ability to support hematopoiesis in vitro. However, to the best of our knowledge, no study so far has prospectively addressed in depth the ability of AA BM-MSC to maintain hematopoietic homeostasis and progenitor function in vitro, their in vivo repopulating function in xenotransplant models, or the immunosuppressive and anti-inflammatory properties on these cells.…”
Section: Discussionmentioning
confidence: 99%
“…32,34 The proliferative and clonogenic capacity of mesenchymal cells (an important immune regulator) in the marrow microenvironment has been reported to be diminished in AA. [46][47][48][49] However, these findings have not been consistent. 50 Nevertheless, an impaired microenvironment could contribute to pathogenesis, limiting support for haematopoiesis and lack of regulatory signals.…”
Section: Immune Systemmentioning
confidence: 84%